AKAD MURABAHAH, IMPLEMETASI DAN TANTANGAN - Irianto Irianto (Valid: Jurnal Ilmiah, 2016)
Islam does not prohibit the form of transaction unless there is an element of injustice in it, such as usury, hoarding (ihtikâr), and other fraud, or indicated the transaction may give rise to discord or hostility between human beings, such as the existence or nature spekulasi.Transaction gharar muamalah built on the principle beneficiaries , Opinions that allows murabahah, aiming to ease the problems of human life. Most contemporary scholars who forbid and proscribe the practice murabaha bi li al-amir al-Syira ', due murabaha transactions in Islamic financial institutions (LKS) and Islamic banks is not intended to make buying and selling but just Hilah or tricks to justify usury. LKS or Islamic banks in the transaction murabaha selling items that have not yet been incorporated (bai'al-a'dum), where the Islamic banks and customers promised to do a murabaha transaction. Murabaha instrument is used only as a transitional step taken in the process of Islamization of the economy. To avoid the practice of Murabahah will be stuck on the practice Hilah, bai''înah, bay'atâni fi bay'ah, and bai 'al-ma'dum (sell buy something that does not exist / owned), then the contemporary scholars require some requirements the practice of buying and selling murabaha in the islamic financial institutions, among others: 1). Murabahah is selling a commodity with strong price including a mutually agreed profit margin. 2). LKS or Islamic banks, must have purchased commodities / goods and store in his power, or buy through a third person as his agent before being sold to its customers. But if the direct purchase to the supplier is not practical, it is permissible for customer financing provider to utilize as an agent / representative with the use wakalah to buy necessary commodities on behalf of the financing